A study of effectiveness of addition of drug teneligliptin to metformin, glimepiride, pioglitazone combination in type II diabetic patients - Patil, Dilip Pandurang (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes is a most prevalent chronic disease and has reached to alarming stage in almost all developed and developing countries. Worldwide approximately four hundred millions of people are living with diabetes and it is a leading cause of death. Aims and objectives is to study effectiveness of addition of drug Teneligliptin to Metformin, Glimepiride, Pioglitazone combination in type II Diabetic patients. Methods: This was a cross sectional study carried out in the department of Medicine of a tertiary health care centre during the one year period i.e. January 2017 to January 2018 in the type II diabetic patients. Out of all type II diabetic patients 40 patients who were on the treatment for hypoglycemia with drugs Metformin, Glimepiride, Pioglitazone were selected out of these randomly 20 patients were continued on the previous treatment (Group B) and remaining 20 were given additional drug Teneligliptin (Group A). The statistical analysis was done by unpaired t-test and chi-square test analyzed by SPSS 19 version of software. Results: In this study Authors have seen that the average age in both the groups was comparable i.e. 36.78±6.74 and 38.92±5.87 (p>0.05, t=1.24, df=38), the sex ration was also similar in both the group (p>0.43, χ2=0.43, df=1) and the HbA1C was comparable at 1st Wk. 10±4.56 - 9.87±3.42 (p>0.05, t=1.023, df=38) and 4th Wk. 8±5.23 - 9.67±4.52 (p>0.05, t=1.0804, df=38) but significantly differed at 8th Wk. 7.12±2.34 - 9.92±3.56 (p<0.01, t=3.82, df=38), 12th Wk. 5.98±1.98 - 9.24±2.79 (p<0.001, t=4.26, df=38) respectively in Group A and B. Conclusions: It can be concluded from this study that the addition of Teneligliptin significantly reduced the HbA1c level at the end of 4th wk. and hence superior to conventional Metformin, Glimepiride, Pioglitazone only combination treatment.